2016
DOI: 10.1039/c5cc07090b
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobized plant polyphenols: self-assembly and promising antibacterial, adhesive, and anticorrosion coatings

Abstract: Hydrophobized plant polyphenols can be easily prepared by rational and controlled etherification of highly abundant aromatic hydroxyls with linear alkyl chains. The resultant organo-soluble polyphenols spontaneously formed fibrous structures and unravelled to be potential adhesive, anticorrosion, and antibacterial coatings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 38 publications
1
40
0
1
Order By: Relevance
“…Traditionally, phenolic-based materials have been used as pigments, antioxidants, photographic developers, and inks. [70] However, in recent times, their broad range chemical properties and functions have made them useful precursors for constructing a range of smart, advanced materials including stimuli-responsive materials, [192,193] antibacterial and chemical-resistant materials, [194,195] superstructures, [128] unique polymeric materials, [196] DNA origami-based materials, [197] and other nanosystems. [198,199] Moreover, natural polyphenols have recently been shown to provide enhanced blood circulation after complexation with proteins.…”
Section: Applicationsmentioning
confidence: 99%
“…Traditionally, phenolic-based materials have been used as pigments, antioxidants, photographic developers, and inks. [70] However, in recent times, their broad range chemical properties and functions have made them useful precursors for constructing a range of smart, advanced materials including stimuli-responsive materials, [192,193] antibacterial and chemical-resistant materials, [194,195] superstructures, [128] unique polymeric materials, [196] DNA origami-based materials, [197] and other nanosystems. [198,199] Moreover, natural polyphenols have recently been shown to provide enhanced blood circulation after complexation with proteins.…”
Section: Applicationsmentioning
confidence: 99%
“…1,2 It consists of a center glucose molecule with all five hydroxyl moieties esterified with two gallic acid (3,4,5-trihydroxybenzoic acid) molecules. The trihydroxylphenyl groups play an important role in binding a variety of substrates through chemical and physical interactions, [3][4][5][6][7][8][9][10][11][12][13] which are similar to the adhesion mechanism of 3,4-dihydroxyphenylalanine (DOPA)-enriched adhesive proteins of blue mussels. 14 TA can be deposited onto various organic and inorganic substrates because of its inherent affinity towards surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the partial substitution of hydrophilic hydroxyl groups by hydrophobic alkyl bromide moieties may facilitate the layer‐by‐layer deposition due to the adoption of an amphiphilic TA‐Br molecular. Consequently, the hydrophobic alkyl bromides tend to become positioned at one side of the TA‐Br molecule and the hydrophilic hydroxyl groups tend to become localized at the other side, rather than undergoing the random aggregation that is observed with pristine TA molecules . Based on the following two measurements, it could be concluded that the surface of glass was completely covered by a TA layer.…”
Section: Resultsmentioning
confidence: 92%
“…WILEYONLINELIBRARY.COM/APP the hydrophobic alkyl bromides tend to become positioned at one side of the TA-Br molecule and the hydrophilic hydroxyl groups tend to become localized at the other side, rather than undergoing the random aggregation that is observed with pristine TA molecules. 36 Based on the following two measurements, it could be concluded that the surface of glass was completely covered by a TA layer. First, silica elements could not be detected via XPS due to the depth limitation of 10 nm for XPS measurements, while the number ratio of C/O/Br atoms was 60.52/38.3/1.17 (Table I), which was similar to that revealed via 1 H NMR characterization.…”
Section: Articlementioning
confidence: 93%